Sikap Keuangan Memediasi Pengaruh Literasi Keuangan dan Self-Control Terhadap Perilaku Pengelolaan Keuangan - Amanda Septia Ningsih; Ma'rufatur Rodhiyah (Jurnal Ekonomi Manajemen Akuntansi, 2026)
This study aims to analyze and examine the effect of financial literacy and self-control on financial management behavior, with financial attitude as an intervening variable among accounting students at universities in Lamongan. This research employed a quantitative approach using a survey method through questionnaire distribution via Google Form. The population consisted of accounting students at universities in Lamongan, with a total sample of 232 respondents selected using probability sampling with a simple random sampling technique. Data analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM) version 4.0. The results indicate that financial literacy does not have a significant effect on financial management behavior, while self-control has a significant effect on financial management behavior. Furthermore, financial literacy and self-control significantly influence financial attitude, and financial attitude significantly affects financial management behavior. Financial attitude is also proven to significantly mediate the relationship between financial literacy and self-control on financial management behavior.